Performance and drag during drafting swimming in highly trained triathletes - Chatard, J. C.; Chollet, D.; Millet, G. (Medicine & Science in Sports & Exercise, 1998)
The influence of drafting was studied on the swimming performance, metabolic response, and passive drag of triathletes (N = 8). Result: Swimming behind another swimmer in a race is advantageous for triathletes.